Flexible nanopositioning actuators based on functional nanocomposites. (20th January 2020) - Chen, Hairong; Liu, Wanwan; Xia, Hong; Qiu, Yiping; Ni, Qing-Qing; Fu, Yaqin
Abstract: Nanopositioning actuators play a vital role in nanofabrication technologies, but existing nanopositioning actuators are typically made of rigid materials. Here, considering the advantages of soft actuators such as lightweight and good adaptability, we developed a kind of flexible actuators which could realize nanopositioning in a simple way. These actuators were made of functional nanocomposites which were compounded by lead zirconate titanate, shape memory polyurethane and silver nanoparticles. The results showed the ability to generate displacements with positioning errors within ±5 nm and the ease to be deformed into desired shapes. Moreover, no special requirement for the realization of nanopositioning also revealed the promising potential for decreasing the costs.